(untitled) (Sustainable Construction (SUSCON), 2024)
Regional General Hospital RSUD Dr Sam Ratulangi Tondano is one of the important projects which started on 09 August 2021 with plans for completion on 2 April 2023 This project has a total project value of Rp 115 093 322 000 which reflects the scale and serious commitment to developing health infrastructure in the region However from January 23 2023 to January 29 2023 this project experienced a deviation of 0 98 This deviation is caused by several factors that can indicate delays in the construction of this project In this research fast track is used as a data analysis method With data collection techniques using interviews and direct observation The optimum duration for the implementation of the Dr RSUD construction project Sam Ratulangi Tondano using the Fast Track method was 546 days from the normal duration of 600 days or around 9 The project cost was reduced by IDR 517 919 949 or around 0 45 of the initial project cost This is due to a reduction in project duration which has an impact on indirect project costs If a fine system is implemented the project cost will be Rp 121 308 361 388 or a fine of Rp 6 215 039 388 for 54 days of delay < p>